PENGARUH KOMPENSASI DAN JOB EMBEDDEDNESS TERHADAP TURNOVER INTENTION PADA KARYAWAN - Putri, Nazlina Dwi; Siregar, Onan Marakali (Jurnal Ilmiah Wahana Pendidikan, 2024)
Several things can reduce turnover intention in employees, namely by implementing fair company compensation and by using the concept of job embeddedness to see an employee's interest in the company. This study aims to determine how the effect of compensation and job embeddedness on turnover intention in employees of PT Bank Rakyat Indonesia, Iskandar Muda Medan branch. This form of research is quantitative research with an associative approach. The population used in this study were employees of PT Bank Rakyat Indonesia, Iskandar Muda Medan branch, with a sample of 55 respondents with sampling techniques using the Slovin formula. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analyses, partial tests, simultaneous tests, and determination coefficient tests. The results of this study indicate that the compensation and job embeddedness variables have a positive and significant effect both partially and simultaneously on turnover intention, and have an effect of 56.4%, while the remaining 43.6% is influenced by other factors outside this research model.